Answer: y = x/2 + 3
Explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c represents the y intercept.
m represents the slope of the line.
m = (y2 - y1)/(x2 - x1)
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
From the graph,
y2 = 6
y1 = 3
x2 = 6
x1 = 0
Slope,m = (6 - 3)/(6 - 0) = 3/6 = 1/2
To determine the y intercept, we would substitute x = 6, y = 6 and m= 1/2 into y = mx + c. It becomes
6 = 6 × 1/2 + c
6 = 3 + c
c = 6 - 3
c = 3
The equation becomes
y = x/2 + 3